Contestation of Islamic Educational Ideology in Pesantren - Khabibah, Siti; Marhumah; Suhadi; bin Ahmad, Khadher (Cendekia: Kependidikan dan Kemasyarakatan, 2024)
This study examines life's different ideas, values, and views, which are the basis of pesantren's thinking and philosophy. It leads to the contestation of educational ideology in determining the ways, values, and methods in pesantren’s education. Influenced by the Naqsabandiyah-Kholidiyah order, it emphasises traditional salafiyyah sorogan learning methods alongside practices of spiritual discipline, or tirakat, to deepen Islamic understanding. Over time, however, this foundation was supplanted by a diniyyah educational ideology, which structured classroom learning around classical texts and adopted the missionary methods of the tabligh cong-regation. It emphasises adherence to the Sunnah and mosque-centered outreach, which became central to Al Fatah Temboro's philosophy. Data collection for this study involved direct and indirect observations, structured interviews with key informants, and analysis of pesantren documentation. Data were then reduced, categorised, and verified through triangulation to ensure accuracy. The findings reveal that ideological competition within Al Fatah Temboro eventually led to establishing a unique ideology that defines the institution today. It becomes one of the greatest pesantren in Indonesia, with the diniyyah education system: Jamaah Tabligh, called as diniyyah jamaah tabligh.